1999
DOI: 10.3109/10611869909085505
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Norfloxacine Release from Tablet Coated with a New pH-Sensitive Polymer, P-4135F

Abstract: A new pH-sensitive polymer, P-4135F, was evaluated as a colon delivery device for norfloxacine (NFLX) which is used for the therapy of patients with Vero toxin-producing Escherichia coli gastroenteritis. P-4135F has a dissolution threshold pH of 7.2 which is higher than the conventional pH-sensitive polymers, Eudragit S100 and L100. To compare the dissolution site of P-4135F coated tablets with other enteric polymer coatings, mini-tablets containing sodium fluorescein (FL) as a model drug were prepared by coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Compared to the other pH-sensitive polymers, Eudragit P-4135F dissolves at a pH around 7.2, allowing a further retention of drug release toward the colonic tissue (18,19). This report evaluates the mitigating potential of FK506 in IBD when delivered locally to the colon after oral administration by a microparticulate delivery system based on Eudragit P-4135F.…”
Section: Introductionmentioning
confidence: 96%
“…Compared to the other pH-sensitive polymers, Eudragit P-4135F dissolves at a pH around 7.2, allowing a further retention of drug release toward the colonic tissue (18,19). This report evaluates the mitigating potential of FK506 in IBD when delivered locally to the colon after oral administration by a microparticulate delivery system based on Eudragit P-4135F.…”
Section: Introductionmentioning
confidence: 96%
“…The pH in the terminal ileum could rise to 7.5; hence, the delivery devices coated with these polymers have a tendency to release their drug load before reaching the colon, and are more appropriately defined as ileo-colonic delivery systems 10 . A recently developed copolymer of methyl acrylate, methyl methacrylate, and methacrylic acid 11,12 is commercially available as Eudragit ® FS 30 D 10 . This polymer has a similar threshold dissolution pH as Eudragit ® S, but dissolves in a slower and more controlled manner 13 .…”
Section: Introductionmentioning
confidence: 99%
“…and to deliver peptides and proteins to the colon for systemic absorption. 5 Strategies for delivering orally administered drugs to the colon include the use of prodrugs, 6 colon-specific biodegradable polymers, 7-9 coatings with pH-sensitive polymers, [10][11][12][13][14][15] and timed-release systems. [16][17][18] However, in some delivery systems, especially those by using pH-sensitive polymers, drugs were released in the terminal ileum before dosage forms reached the colon.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] However, in some delivery systems, especially those by using pH-sensitive polymers, drugs were released in the terminal ileum before dosage forms reached the colon. For example, it has been shown that tablets coated with Eudragit P-4135F, a new pH-sensitive polymer with a dissolution threshold pH of 7.2, disintegrated in the lower region of the small intestine of rats, 13 and polymeric microspheres of Eudragit P-4135F encapsulating ellagic acid could deliver the drug to the terminal ileum and the colon. 14 We have already developed hypromellose acetate succinate (HPMCAS, Fig.…”
Section: Introductionmentioning
confidence: 99%